2012
DOI: 10.1039/c2cp41762f
|View full text |Cite
|
Sign up to set email alerts
|

Small carbides of third-row main group elements: structure and bonding in C3X compounds (X = K–Br)

Abstract: The molecular structures of third-row main group tricarbides C(3)X (X = K-Br) have been studied by quantum chemical methods. It is found that less electronegative elements (K, Ca, Ga, Ge) favor either fan or rhombic structures (resulting from side interactions with either linear or triangular C(3) units), whereas the more electronegative elements (As, Se, Br) favor linear or three-membered ring structures (resulting from σ-type interactions with either linear or triangular C(3) units). The predicted global min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…In the case of UC 3 , a similar behavior was observed: 11 the fan isomer was also predicted as the global minimum. In addition, a systematic study of third row main group tricarbides 32 has shown that fan or rhombic isomers are favored for less electronegative elements, whereas for more electronegative elements, three-membered rings or linear species are preferred. Uranium and plutonium, both having low electronegativities, behave like electropositive atoms such as K or Ca rather than like electronegative atoms such as Se or Br.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In the case of UC 3 , a similar behavior was observed: 11 the fan isomer was also predicted as the global minimum. In addition, a systematic study of third row main group tricarbides 32 has shown that fan or rhombic isomers are favored for less electronegative elements, whereas for more electronegative elements, three-membered rings or linear species are preferred. Uranium and plutonium, both having low electronegativities, behave like electropositive atoms such as K or Ca rather than like electronegative atoms such as Se or Br.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In a systematic study of small carbides for third-row main group elements, 29 it was found that the more electronegative elements (As, Se, Br) favor linear or threemembered ring structures, whereas less electronegative elements (K, Ca, Ga, Ge) clearly prefer either fan or rhombic isomers. Uranium, with low ionization energy, behaves in a similar way as other electropositive elements such as K or Ca.…”
Section: Resultsmentioning
confidence: 99%
“…In organometallics, the C 3 Se species has been used as a bridging ligand [27]. Some previous information on carbon-selenium species has been obtained from quantum-chemical calculations, albeit at rather modest levels of theory [26,[28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%